2000
DOI: 10.1046/j.1365-246x.2000.00211.x
|View full text |Cite
|
Sign up to set email alerts
|

The major asperities of the 1999Mw = 7.4 Izmit earthquake defined by the microseismicity of the two decades before it

Abstract: Summary We compare the rupture location of the Mw 7.4 Izmit earthquake to the local seismic hazard estimated by the technique of mapping local recurrence time, TL, based on the microseismicity. After correcting for a magnitude shift in 1990, the declustered earthquake catalogue, produced by the University of Istanbul for the Marmara Sea region, is homogeneous for Md ≥ 2.9 during 1983–1999. We mapped TL in the area bounded by 40°–41° latitude and 27.6°–30.5° longitude. TL is the probabilistic estimate of recurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 30 publications
4
35
0
Order By: Relevance
“…3) verify high seismic activity in the region (Crampin and Ü çer 1975;Dewey 1976;Ayhan et al 1984;Ambraseys and Finkel 1987;Kalafat et al 2000;Ö ncel and Wyss 2000;Ö zalaybey et al 2002).…”
Section: Seismicitymentioning
confidence: 92%
See 2 more Smart Citations
“…3) verify high seismic activity in the region (Crampin and Ü çer 1975;Dewey 1976;Ayhan et al 1984;Ambraseys and Finkel 1987;Kalafat et al 2000;Ö ncel and Wyss 2000;Ö zalaybey et al 2002).…”
Section: Seismicitymentioning
confidence: 92%
“…In spite of some successes, the concept is indicated to be still in the testing process (Wyss and Matsumura 2002). Spatial mapping of FMD over the surface area bounded by 40°-41°N latitude and 27.6°-30.5°E longitude in the Marmara region has been previously implemented by Ö ncel and Wyss (2000) using the background M D C 2.9 microseismicity data covering the time period post-1983 and prior to 1999 _ Izmit mainshock. They obtained strong spatial variability of b values in the range 0.9-1.6 in the Sea of Marmara.…”
Section: Comparison Of Historically Observed Recurrence Times With Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Current investigations have definitely confirmed that the majority of the long-term fault slip occurs along the offshore section of the northern fault segment following the northwest striking Prince Island Fault (PIF) combined with the eastwest striking Central Marmara Fault (CMF) immediately south of Istanbul (Le Pichon et al 2001;Armijo et al 2005;Ergintav et al 2014). Together with seismological and seismotectonic studies (Gürbüz et al 2000;Oncel and Wyss 2001;Oncel and Wilson 2006;Kalafat et al 2011), recent GPS and kinematic studies (Meade et al 2002;Flerit et al 2003) have indicated that the northern branch of the NAFZ is more active and also creates much larger motion than the southern branch. This hypothesis has also been verified by historical period (Ambraseys and Jackson 2000;Ambraseys 2001aAmbraseys , b, 2002a, instrumental period (Kalafat et al 2011), and recent detailed microearthquake seismicity studies (Sato et al 2004;Bohnhoof et al 2013).…”
Section: Introductionmentioning
confidence: 83%
“…It is conventional that the global average of b-value is approximately one (e.g. Oencel and Wyss, 2000) but it has not been extended to some cases of seismicity such as induced seismicity (Nuannin, 2006) and volcanic areas (Schorlemmer et al, 2003). The regional variations of b-value are found to have a correlation with stress level variations.…”
Section: Correlation Between B-value and Water Levelmentioning
confidence: 99%